Ligand-Cyclometallation on Rh(I) Complexes Initiated by Cyclic Organotin Compounds Leads Oxidatively to Rh(III) Analogues - A.K. AL-Allaf, Talak (Asian Journal of Chemistry, 2010)
Reactions of [RhCIL3], where L = PEt3, PBU3n, PPh3, with (R2Sn)n (in slight excess), where R = Me or Ph, n = 6 and R = Et. n = 9, were carried out in the hope of obtaining rhodium(l) complexes formed by insertion of R2Sn moieties into Rh—Cl bonds. The 31P NMR spectral data of the reaction mixtures showed that no Rh—Sn species could be detected in the products, but rather an interesting new complex, formed by cyclometallation involving a β-hydrogen transfer from the ligands PEt3 or PBu3n, or from the ortho-carbanato of the phenyl group of PPh3 in the complexes [RhClL3], to form the Rh(III) complexes. Explanations of such results are given and discussed.